PENJUALAN PRODUK iB HASANAH CARD MELALUI PROMOTION MIX PADA BNI SYARIAH CAB. KOTA PALANGKA RAYA - Jirhanuddin Jirhanuddin; Jelita Jelita; hasanah hasanah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2016)
Promotion and selling is an important function that the key to successful banking operations. Banks should be able to see the needs and tastes of the dynamic market with highly competitive conditions. Moreover, products and services in Islamic banking is still new and is not widely known to the public so it must have its own character in the marketing and sales strategies. And here the authors are interested in researching the product sales iB Hasanah Card through the promotion, because it is supported also by the narrative of one of the employees of BNI sharia city of Palangkaraya stating that there is significant influence on variables Promotion product mix on sales volume iB Hasanah this card, plus another in 2015, Bank Indonesia (BI) has issued rules restricting the credit card ownership by age and income.The formulation of the problem in this research; (1) How does the product characteristics iB Hasanah card (2) How can the sale of products iB Hasanah Card. This field research using qualitative descriptive approach, which is the object of research is the sale of products through the iB Hasanah Card Promotion mix on BNI Syariah Cab. While the research subjects were 2 employees in positions related. Methods of data collection using observation, interviews, and documentation. While the validity of the data is also attested by the triangulation technique, and then the data were analyzed through the method of collection, reduction, display, and Conclusions.With a wide range of references theory used to support the research, the results showed that, the sale of products iB Hasanah Card through the promotion mix that has the largest percentage is advertising, which have a percentage of both is personal selling, the third is a public relations (public relations) or publicity and the percentage The fourth is a sales promotion. Where the largest percentage occurred in 2015 which amounted to 4.18% and the lowest percentage occurred in 2012 which amounted to 1.45%. Based on the results of the above data can be authors conclude also that in 2014 to 2015 only the advertising decreased from 65.97% to 60.38% it reinforces the reasons of the problems occurred that a change in Bank Indonesia Regulation No.14 / 2 / PBI / 2012 dated January 6, 2012 on Amendment to Bank Indonesia Regulation Number 11/11 / PBI / 2009 regarding Organization Card Payment Instrument.